ANALISA KESADARAN WISATA MASYARAKAT DESA WISATA KEBON AGUNG KECAMATAN IMOGIRI KABUPATEN BANTUL TERHADAP MINAT KUNJUNG WISATAWAN - Kiswantoro, Amin; Wicaksana, Sabda Riesa (Kepariwisataan: Jurnal Ilmiah, 2016)
This journal was written to explain the affection of tourism awareness of society to visiting desire of visitor to a destination. In this paper the matters are narrow into a area that called Tourism Village of Kebon Agung that located in Imogiri, Bantul, Yogyakarta. There are some factors that affect visiting desire and one of them is Tourism Awareness. An tourism attraction without support from society that life around that has tourism awareness seems has low value to sell, by that case the author rise this theme and did a research in Desa Wisata Kebon Agung by used quantitative analyzing with Pruduct-moment equality as the best approaching and show up how far the affect of society tourism awareness to visiting desire. The research tool is questioner and the result of analyzing is the society tourism awareness has high level affect to visit desire. This result is best for area around Kebon Agung and possibility has a same thing with another village. It is a good thing if society are aware with tourism, start from where they living and finally develop national tourism. Keywords: Affection, Tourism, Society